Long-period grating based coupler for multi-core fiber systems - Sousa, Liliana M. (2021)
In this work, we propose and demonstrate numerically a long-period grating (LPG) based technique to couple light from a single-mode fiber (SMF) to all cores of a multi-core fiber (MCF), i.e., an SMF to MCF coupler. The light launched into the SMF core is coupled to the SMF cladding due to the LPG inscribed in the core. Then, the optical power is transferred between fibers claddings, enhanced by the reduction of the SMF cladding radius. Finally, the MCF cladding optical power is distributed by all cores of the MCF due to identical LPGs inscribed in them. We use the coupled-mode theory to study and design the proposed device. We achieve a coupling efficiency of approximately 90% of the input power in a total length of 15.1 cm. We also study the coupler’s sensitivity to the SMF radius and LPGs period. Results show that the proposed device can improve the pumping efficiency of MCF amplifiers.